Using Intermittent Fasting as a Non-pharmacological Strategy to Alleviate Obesity-Induced Hypothalamic Molecular Pathway Disruption - Oliveira, Luciana da Costa; Morais, Gustavo Paroschi; Ropelle, Eduardo R.; de Moura, Leandro P.; Cintra, Dennys E.; Pauli, José R.; de Freitas, Ellen C.; Rorato, Rodrigo; da Silva, Adelino Sanchez R. (Frontiers in Nutrition, 2022)
Intermittent fasting (IF) is a popular intervention used to fight overweight/obesity. This condition is accompanied by hypothalamic inflammation, limiting the proper signaling of molecular pathways, with consequent dysregulation of food intake and energy homeostasis. This mini-review explored the therapeutic modulation potential of IF regarding the disruption of these molecular pathways. IF seems to modulate inflammatory pathways in the brain, which may also be correlated with the brain-microbiota axis, improving hypothalamic signaling of leptin and insulin, and inducing the autophagic pathway in hypothalamic neurons, contributing to weight loss in obesity. Evidence also suggests that when an IF protocol is performed without respecting the circadian cycle, it can lead to dysregulation in the expression of circadian cycle regulatory genes, with potential health damage. In conclusion, IF may be an adjuvant treatment to improve the reestablishment of hypothalamic responses in obesity.